Breit and QED contributions in atomic structure calculations of tungsten ions. (February 2020) - Kozioł, Karol
Highlights: The calculations performed by FAC, GRASP2K, and MCDFGME codes are compared in selected case studies of radiative transitions occurring in W7+, W57+, and W46+ tungsten ions. Various approaches to include Breit interaction term and QED corrections in atomic calculations has been examined. The presented data may be used to estimate the theoretical uncertainties relevant to interpretation of high-resolution spectroscopic data. Abstract: The Fac, Grasp2k, and Mcdfgme codes are compared in three case studies of the radiative transitions occurring in tungsten ions: (i) Ni1 and Ni2 lines in Ni-like tungsten, (ii) 3 p 3 / 2 − 3 p 1 / 2 fine splitting in Cl-like tungsten, and (iii) Kα 1 and Kα 2 lines in W VIII. Various approaches to including the Breit interaction term and QED corrections in atomic calculations are examined. Electron correlation effects are also investigated and compared to the Breit and QED contributions. The data presented here may be used to estimate theoretical uncertainties relevant to interpretation of high-resolution spectroscopic data.